2011
DOI: 10.1098/rsif.2011.0207
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mechanisms of increased eggshell hardness of avian brood parasites relative to host species

Abstract: Obligate brood parasitic birds lay their eggs in nests of other species and parasite eggs typically have evolved greater structural strength relative to host eggs. Increased mechanical strength of the parasite eggshell is an adaptation that can interfere with puncture ejection behaviours of discriminating hosts. We investigated whether hardness of eggshells is related to differences between physical and chemical traits from three different races of the parasitic common cuckoo Cuculus canorus, and their respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 70 publications
1
42
0
Order By: Relevance
“…However, the evolution of eggshell coloration and the underlying pigment composition in brood parasite eggs may be driven not only by host discrimination of brood parasitic eggs, but also by shared environmental conditions [56]. Interacting effects of host and parasite maternal investment may also affect egg pigmentation and visible phenotype [10]. In parallel with our analyses of spectral and perceptual colour metrics, the chemical analyses revealed that in two of the three host-parasite systems, the concentrations of biliverdin and protoporphyrin in the cuckoo eggshells were more similar to local host eggshells compared with either local non-host or non-local host eggshells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evolution of eggshell coloration and the underlying pigment composition in brood parasite eggs may be driven not only by host discrimination of brood parasitic eggs, but also by shared environmental conditions [56]. Interacting effects of host and parasite maternal investment may also affect egg pigmentation and visible phenotype [10]. In parallel with our analyses of spectral and perceptual colour metrics, the chemical analyses revealed that in two of the three host-parasite systems, the concentrations of biliverdin and protoporphyrin in the cuckoo eggshells were more similar to local host eggshells compared with either local non-host or non-local host eggshells.…”
Section: Discussionmentioning
confidence: 99%
“…15) are primary hosts and many of them are not suitable hosts at all [1,7]. The cuckoo has evolved several strategies to decrease or circumvent the rejection of its eggs by the hosts, including the laying of relatively small eggs [8], the formation of both absolutely and relatively thicker eggshells [9][10][11], and, perhaps its best-known adaptation, the avian-perceived mimicry of host egg colours and maculation patterns [12][13][14] (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Significant deviations from these values would arise if puncture attacks were biased towards one or the other egg type [35], and/or if eggs frequently resisted puncture when attacked. In the case of parasite eggs, the latter at least is expected to be at play, given that cowbird eggs are structurally adapted to reduce their vulnerability to breakage, being rounder and thicker-shelled than those of their hosts and non-parasitic relatives [36][37][38][39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…The fact that cuckoo eggshell thickness has decreased in this host species indicates indirectly that maintenance of this trait is costly and given no selection for it exerted by the host, it will not persist. More recently, Igic et al (2011) compared cuckoo eggshell strength in three European cuckoo host races, by using several advanced mechanical measures including micro-structural strength analysis, failed to find significant differences among host races. Thus, a larger sample of host species and their host races of brood parasites, including a wider spectrum of hosts in terms of their egg rejection frequencies and modes of rejection, are needed to rigorously test these findings.…”
Section: Perspectives and Avenues For Future Researchmentioning
confidence: 99%
“…This indicates that eggshell strength may be an adaptation to their brood parasitic life-style. Eggshell strength is achieved by increased eggshell thickness, rounder shape, higher eggshell density and enhanced micro-hardness; the contribution of these mechanisms may differ among brood parasitic taxa (Picman, 1989;Brooker and Brooker, 1991;Picman and Pribil, 1997;Igic et al, 2011). Eggshells contain up to 98% calcium and many birds have been shown to be calcium-limited during laying (reviewed in Reynolds et al, 2004).…”
Section: Introductionmentioning
confidence: 99%